HUBUNGAN LAMA KERJA DENGAN KEPATUHAN PERAWAT DALAM MELAKSANAKAN SOP PEMASANGAN INFUS DI RSUD BALARAJA TAHUN 2022 - Melia Rizka Safitri; Bayu Imanuddin; Febi Ratnasari (Nusantara Hasana Journal, 2022)
The nurse’s compliance in applying the SOP for infusion is marked by the obligation to complete the infusion according to the SOP that has been set with the aim of reducing problems due to infusion. Compliance is very important for the way the individual behaves concerned to obey or submit to something. The purpose of the study was to determine the relationship between length of work and nurse compliance in implementing the SOP for infusion at the Balaraja Hospital, Kab. Tangerang. This research was conducted with a descriptive quantitative research design with a cross sectional approach. With consecutive sampling technique, the sample is 133 respondents. Based on the results of research conducted that 133 respondents obtained length of work with the results strongly agree 80 respondents (60.2%) then obtained results that disagree as many as 53 respondents (39.8%). Meanwhile, the results of nurse compliance in the obedient category were 93 respondents (59.4%). While the category of less obedient as many as 40 respondents (40.6%). Then the results obtained were 97 respondents (72.9%) of nurses who carried out the SOP for infusion in the correct category, then the results obtained were 36 respondents (27.1%) nurses who performed the SOP for infusion with the wrong category, analyzed by Chi Square test, obtained p value = 0.002 < 0.05, it can be stated that Ho is rejected, Ha is accepted, meaning that there is a significant relationship between the length of work and the SOP for infusion. It was concluded that there was a relationship between length of work and nurse compliance in implementing the SOP for infusion at the Balaraja Hospital, Tangerang.